Emerging agents for the treatment and prevention of stroke: progress in clinical trials. (3rd October 2021) - Safouris, Apostolos; Magoufis, Georgios; Tsivgoulis, Georgios
ABSTRACT: Introduction: Recent years have witnessed unprecedented progress in stroke care, but unmet needs persist regarding the efficacy of acute treatment and secondary prevention. Novel approaches are being tested to enhance the efficacy of thrombolysis or provide neuroprotection in non-thrombolized patients. Areas covered: The current review highlights pharmaceutical agents under evaluation in clinical trials concerning the acute, subacute, and chronic phase post-stroke. We examine the evidence in favor of tenecteplase as an alternative thrombolytic drug to alteplase, nerinetide as a promising neuroprotective agent, and glibenclamide for reducing edema in malignant hemispheric infarction. We discuss the use of ticagrelor and the promising novel category of factor XI inhibitors in the subacute phase after stroke. We offer our insights on combined rivaroxaban and antiplatelet therapy, PCSK-9 inhibitors, and other non-statin hypolipidemic agents, as well as novel antidiabetic agents that have been shown to reduce cardiovascular events in the long-term. Expert opinion: Current approaches in stroke treatment and stroke prevention have already transformed stroke care from a linear one-for-all treatment paradigm to a more individualized approach that targets specific patient subgroups with novel pharmaceutical agents. This tendency enriches the therapeutic armamentarium with novel agents developed for specific stroke subgroups. Abbreviations: IVT: intravenous thrombolysis; RCTs: randomized-controlled clinical trials; TNK: Tenecteplase; COVID-19: Coronavirus 2019 Disease; EXTEND-IA TNK: The Tenecteplase versus Alteplase Before Endovascular Therapy for Ischemic Stroke trial; AIS: acute ischemic stroke; NNT: number needed to treat; MT: mechanical thrombectomy; sICH: symptomatic intracranial hemorrhage; mRS: modified Rankin Scale; AHA/ASA: American Heart Association/American Stroke Association; ESO: European Stroke Organization; NA-1: Nerinetide; ENACT: Evaluating Neuroprotection in Aneurysm Coiling Therapy; CTA: CT angiography; TIA: transient ischemic attack; CHANCE: Clopidogrel in High-risk patients with Acute Non-disabling Cerebrovascular Events; LOF: loss-of-function; PRINCE: Platelet Reactivity in Acute Nondisabling Cerebrovascular Events; THALES: Acute Stroke or Transient Ischemic Attack Treated with Ticagrelor and ASA [acetylsalicylic acid] for Prevention of Stroke and Death; CHANCE-2: Clopidogrel With Aspirin in High-risk Patients With Acute Non-disabling Cerebrovascular Events II; FXI: Factor XI; PACIFIC-STROKE: Program of Anticoagulation via Inhibition of FXIa by the Oral Compound BAY 2433334—NonCardioembolic Stroke study; COMPASS: Cardiovascular Outcomes for People Using Anticoagulation Strategies; CANTOS-ICAD: Combination Antithrombotic Treatment for Prevention of Recurrent Ischemic Stroke in Intracranial Atherosclerotic Disease; SAMMPRIS: Stenting and Aggressive Medical Therapy for Preventing Recurrent Stroke in Intracranial Stenosis; WASID: Warfarin–Aspirin Symptomatic Intracranial Disease; SPARCL: Stroke Prevention by Aggressive Reduction in Cholesterol Levels; LDL-C: low-density lipoprotein cholesterol; TST: Treat Stroke to Target; IMPROVE-IT: Improved Reduction of Outcomes: Vytorin Efficacy International Trial; PCSK9: proprotein convertase subtilisin–kexin type 9; FOURIER: Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk; CLEAR: Cholesterol Lowering via Bempedoic acid, an ACL-inhibiting Regimen; REDUCE-IT: Reduction of Cardiovascular Events With EPA Intervention Trial; STRENGTH: Outcomes Study to Assess STatin Residual Risk Reduction With EpaNova in HiGh CV Risk PatienTs With Hypertriglyceridemia; ACCORD: Action to Control Cardiovascular Risk in Diabetes; ADVANCE: Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation; VADT: Veterans Affairs Diabetes Trial; GLP-1R: Glucagon-like peptide-1 receptor; SGLT2: sodium–glucose cotransporter 2; CONVINCE: COlchicine for preventioN of Vascular Inflammation in Non-CardioEmbolic stroke; PROBE: Prospective Randomized Open-label Blinded Endpoint assessment.